1992
DOI: 10.3109/00365529209000107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ketogenesis in Seriously Reduced Hepatic Mitochondrial Redox State an Analysis of Survivors and Non-Survivors in Critically Ill Hepatectomized Patients

Abstract: Ketogenesis was evaluated in 33 critically ill hepatectomized patients in relation to the arterial ketone body ratio (acetoacetate to 3-hydroxybutyrate), which reflects hepatic mitochondrial redox state. In 15 patients whose arterial ketone body ratio decreased to below 0.4, blood ketone body levels were significantly increased concomitant with marked increase of blood lactate and plasma alanine levels. In the 6 survivors of these 15 patients, the arterial ketone body ratio was restored within the next 2 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The importance of our findings is twofold. First, markers of mitochondrial dysfunction can be used for earlier diagnosis of PHLF . Currently, diagnosis of PHLF is only possible on or beyond the fifth postoperative day, and predicting liver dysfunction earlier would be attractive .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of our findings is twofold. First, markers of mitochondrial dysfunction can be used for earlier diagnosis of PHLF . Currently, diagnosis of PHLF is only possible on or beyond the fifth postoperative day, and predicting liver dysfunction earlier would be attractive .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the liver performs a myriad of functions, and in addition to filtering toxins, plays a unique role in the regulation of blood glucose homeostasis, crucial for normal cerebral function, since the brain neither synthesizes nor stores the required amount of glucose [ 59 ]. As a result, unstable blood glucose and oxygen delivery to the brain, for even a short period, causes brain damage, while chronic deficiency in these substrates leads to irreversible brain injury, thereby triggering cognitive impairment, coma development, and death [ 20 ]. Additionally, when glucose is not readily available, the liver can produce ketone bodies, which are used by the brain as an alternative energy source.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that acute hyperammonemia leads to rapid and significant decrease in both acetoacetate and β-hydroxybutyrate levels in the liver and blood of non-starved rats. This suggests that hepatic ketogenesis can be inhibited immediately after increasing ammonia levels in the liver [ 60 ], highlighting the role of deterioration of homeostatic liver functions in the occurrence of a brain energy crisis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations